MEDIA PEMBELAJARAN POP UP BOOK DENGAN TEKNIK PARALLEL SLIDE UNTUK MENINGKATKAN PRESTASI BELAJAR PESERTA DIDIK MATERI TUMBUHAN IPAS KELAS IV SEKOLAH DASAR - Sri Rahayu; Wahyu Kurniawati kurniawati; Hermawan Wahyu Setiadi setiadi (Jurnal Genta Mulia, 2026)
This study aims to develop a Pop-Up Book learning media integrated with the Parallel Slide technique as an innovative solution to improve student learning outcomes in Science and Social Studies (IPAS) for fourth-grade elementary school students. The research employed the 4D development model, consisting of Define, Design, Develop, and Disseminate”stages. The study was conducted at SD Muhammadiyah Ambarbinangun using interviews, questionnaires, and tests as data collection methods. Validation by media and subject matter experts indicated that the developed media was categorized as highly valid. Effectiveness testing was carried out through pretest and posttest assessments, analyzed using the Shapiro-Wilk test and Paired Sample t-Test.”The results revealed a significance value of 0.000 (p < 0.05), indicating a statistically significant”improvement in student learning outcomes. Student responses reached 90.83%, while teacher responses were recorded at 95%, reflecting a highly positive reception. These findings suggest that the Pop-Up Book media is practical and feasible for use in IPAS learning to enhance student achievement.